Estudo da influência da temperatura na degradação termoquímica da biomassa de avelós (euphorbia tirucalli Linn) - Avelar, Karen Pereira Batista de (2013)
The bio-oil obtained from the pyrolysis of biomass has appeared as inter-esting alternative to replace fossil fuels. The aim of this work is to evaluate the influence of temperature on the yield of products originating from the pyrolysis process of the powder obtained from the dried twigs of avelós (Euphorbia tirucalli), using a rotating cylinder reactor in laboratory scale. The biomass was treated and characterized by: CHNS, moisture, volatiles, fixed carbon and ashes, as well as evaluation of lignin, cellulose and hemicellulose, besides other instrumental techniques such as: FTIR, TG/DTG, DRX, FRX and MEV. The activation energy was evaluated in non-isothemichal mode with heating rates of 5 and 10 oC/min. The obtained results showed biomass as feedstock with potential for biofuel production, because presents a high organic matter content (78,3%) and fixed-carbon (7,11%). The activation energy required for the degradation of biomass ranged between 232,92 392,84 kJ/mol, in the temperature range studied and heating rate of 5 and 10°C/min. In the pyrolysis process, the influence of the reaction temperature was studied (350-520 ° C), keeping constant the other variables, such as, the flow rate of carrier gas, the centrifugal speed for the bio-oil condensationa, the biomass flow and the rotation of the reactor. The maximum yield of bio-oil was obtained in the temperature of 450°C. In this temperature, the results achieved where: content of bio-oil 8,12%; char 32,7%; non-condensed gas 35,4%; losts 23,8%; gross calorific value 3,43MJ/kg; pH 4,93 and viscosity 1,5cP. The chromatographic analysis of the bio-oil produced under these conditions shows mainly the presence of phenol (17,71%), methylciclopentenone (10,56%) and dimethylciclopentenone (7,76%)